2011
DOI: 10.1016/j.curtheres.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin and Long-Term Histopathologic Changes in a Murine Model of Asthma

Abstract: The results of this study suggest that the group receiving glycyrrhizin had amelioration of all established chronic histopathologic changes of lung in the mouse model of asthma. Further studies are needed to evaluate the efficacy of glycyrrhizin in the management of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Consistent with previous reports, our study demonstrated that GA could significantly alleviate the severity of asthma, including airway inflammation and hyperresponsiveness (Supplementary http://onlinelibrary.wiley.com/doi/10.1111/resp.12655/suppinfo). We provide new insights on GA regarding its anti‐inflammatory action by targeting costimulatory pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports, our study demonstrated that GA could significantly alleviate the severity of asthma, including airway inflammation and hyperresponsiveness (Supplementary http://onlinelibrary.wiley.com/doi/10.1111/resp.12655/suppinfo). We provide new insights on GA regarding its anti‐inflammatory action by targeting costimulatory pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, these drugs do not completely cure or modify the progression of asthma. The symptoms return once the treatment is terminated and further, continued use of these drugs may often lead to systemic and as well local side effects [3940]. Thus, identification of novel effective therapeutics is of immense clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin (10 mg/kg, 7 days, p.o.) has beneficial effects on long-term histopathological changes to the respiratory airway in a mouse model of chronic ovalbumin (OVA)-induced asthma (Hocaoglu et al, 2011). In addition, Ma et al (2013) demonstrated that glycyrrhizic acid could suppress IL-4, IL-5, IL-13, and IFN-γ and inhibit both the recruitment of eosinophils and mucus overproduction in mice treated with OVA (Ma et al, 2013).…”
Section: Respiratory Studiesmentioning
confidence: 99%